Evidence Production in Merger Control: The Role of Remedies - Markus Dertwinkel-Kalt; Christian Wey (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We analyze evidence production in merger control as a delegation problem in an inquisitorial competition policy system. The antitrust agency's incentives to produce evidence on the efficiency of a merger proposal depend critically on its action set. Allowing for a compromising remedy solution reduces information acquisition incentives, and could therefore reduce consumer welfare. The effort-frustrating effect of the remedy solution can be eliminated if a remedy solution can be implemented only after evidence on the efficiency of a merger proposal has been produced.
Keywords: L13; L40; K21; 330; merger remedies; merger control; antitrust